Service Management of the Direct Cash Assistance Program in Lasoani Urban Village, Palu City, Central Sulawesi Province - Rudin M.; Bakarbessy, Maria Lea Frensy (Faculty of Law, Universitas Pekalongan, 2024)
This research aims to evaluate the service management of the Direct Cash Transfer Program in Lasoani Village, Palu City, using a normative juridical approach. This Program refers to Article 34 paragraph (1) of the 1945 Constitution, Law No. 11/2009 on Social Welfare, and Law No. 13/2011 on Handling the Poor. The research used descriptive qualitative methods through interviews, observation, and documentation. The results show that a strong legal foundation and systematic planning support the success of this Program. However, obstacles such as budget and administrative delays are still a challenge in implementation. This research confirms the importance of regulatory harmonisation, transparency, and strengthening the capacity of implementers to improve the effectiveness of the Program. Thus, BLT can contribute more to poverty alleviation and social welfare.